Kepemimpinan Profetik: Telaah Kepemimpinan Pendidikan KH. Ahmad Dahlan dan KH. Hasyim Asy’ari - Syafi’in (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
Leadership is interpreted according to each person's perspective. Especially the leadership of Islamic education which so far has received a negative stigma on aspects of education that seem